Pedagogical intersections: ePortfolio practice and essential learning outcomes for 21st century success. (24th July 2021) - Lehman, Regina M.; Mills, Michele D.; Gupta, Richa; Calderon, Olga
Abstract: ePortfolio practice and assessment of essential learning outcomes (ELOs) are well established at LaGuardia Community College (LAGCC). The way in which these practices intersect is via the assessment of authentic student artifacts generated from assignments aligned with ELOs. Student artifacts are deposited into the Core ePortfolio for college‐wide assessment. Benchmark reading data is used to inform ePortfolio practice and pedagogy at the college‐wide and programmatic levels. General Education Core Competencies and Communication Abilities are established across the College and are an integral part of curricular frameworks in all majors. The Core Competencies—Inquiry and Problem Solving, Integrative Learning, and Global Learning—are expressed through the Oral, Written, and Digital Communication Abilities. ePortfolio practice lends itself to the examination of Integrative Learning and Digital Communication. Recognizing ePortfolio as a high‐impact practice, LAGCC developed the Core ePortfolio as a platform for student active engagement in self‐directed learning and reflection about themselves as learners over their entire curricular and co‐curricular experience. Faculty gain a deepened understanding of the student experience and the process of integrative learning.